Implicit and Explicit Attitudes Toward Intimate Partner Violence Against Women: An Exploratory Study - Sanchez-Prada, Andrés (Journal of interpersonal violence, 2021)
There is consistent evidence that attitudes are important in understanding how people react and behave toward victims and perpetrators of intimate partner violence against women. Researchers have typically measured these attitudes through self-reports. However, explicit measures are prone to socially desirable responding. The overall objective of our research is to provide multimethod measures of public attitudes (explicit and implicit) toward intimate partner violence against women. An opportunity sample of 190 Psychology undergraduates (32 men and 158 women) took part in this study and completed two self-reports: the Inventory of Distorted Thoughts about Women and Violence, and the Inventory of Beliefs about Wife Beating. In addition, they completed a personalized Implicit Association Test, the Gender Violence Implicit Association Test. This study provides evidence of the best way to apply the Gender Violence Implicit Association Test (with feedback) and the best procedure for estimating the Implicit Association Test effect (built-in error penalty). The findings are also consistent with previous research and exhibit a significant disparity between explicit and implicit measures of attitudes toward intimate partner violence against women. These findings, although still preliminary, provide interesting information that affirms the need to incorporate implicit measures of attitudes toward intimate partner violence against women into research on this social problem.